Extracorporeal cardiopulmonary resuscitation for breath‐holding spells followed by cardiac arrest due to left main coronary artery stenosis. Issue 3 (27th May 2015) - Ozyilmaz, Isa; Altin, Husnu Fırat; Yildiz, Okan; Erek, Ersin; Ergul, Yakup; Guzeltas, Alper
Abstract Non‐syndromic congenital supravalvular aortic stenosis (SVAS) leads to ventricular hypertrophy and increased oxygen consumption, and when combined with other factors reduces coronary blood flow, potentially resulting in myocardial ischemia and sudden cardiac death. While the anatomic obstruction of coronary circulation is as common in non‐syndromic SVAS as in Williams syndrome, it often remains unacknowledged. Extracorporeal membrane oxygenation (ECMO) is an elective procedure that can be used to support patients with cardiac arrest during diagnosis as a way to reduce cardiopulmonary load in preparation for surgery or further treatment. In this report, we describe the rare case of an infant with severe SVAS and mild valvular pulmonary and left main coronary artery stenosis, as well as breath‐holding spells. After multiple cardiac arrests, the infant underwent diagnostic catheter angiography on ECMO and had the pathology surgically corrected.